Dynamic membrane-assisted fermentation of food wastes for enhancing lactic acid production. (June 2017) - Tang, Jialing; Wang, Xiaochang C.; Hu, Yisong; Ngo, Huu Hao; Li, Yuyou
Highlights: Fermenter was stably operated under acidic conditions for LA production. DM could significantly intercept particles and enhance LA yield. High abundance of Lactobacillus dominated at uncontrolled pH and pH 4. Backwashing could effectively maintain the DM permeability. Abstract: A dynamic membrane (DM) module was inserted into a fermentation reactor to separate soluble products from the fermented mixture to increase lactic acid (LA) production from food wastes under acidogenic conditions (uncontrolled pH, pH 4 and 5). With a high total suspended solid content (20–40 g/L) in the fermenter, a stable DM could be maintained through regular backwashing. By effectively intercepting suspended solids and lactic acid bacteria (LAB), the fermenter was able to increase microbial activity and largely promote LA yield. Hydrolysis and acidogenesis rates increased with pH, and the highest LA yield (as high as 0.57 g/g-TS) was obtained at pH 4. The microbial community analysis showed that the relative abundance of Lactobacillus increased to 96.4% at pH 4, but decreased to 43.3% at pH 5. In addition, the DM could be easily recovered by intercepting larger particles in less than 2 h after each cycle of periodic backwashing.